Tsunami Induced by the Strike‐Slip Fault of the 2018 Palu Earthquake (Mw = 7.5), Sulawesi Island, Indonesia. Issue 6 (16th June 2021) - Ho, Tung‐Cheng; Satake, Kenji; Watada, Shingo; Hsieh, Ming‐Che; Chuang, Ray Y.; Aoki, Yosuke; Mulia, Iyan E.; Gusman, Aditya Riadi; Lu, Chih‐Heng
Abstract: An unusual devastating tsunami occurred on September 28, 2018 after a strike‐slip faulting earthquake in Sulawesi, Indonesia. The induced tsunami struck Palu city with ∼4‐m flow depth. We performed two analyses to investigate the source of the tsunami. We first conducted the teleseismic source inversion and obtained the overall slip distribution of the strike‐slip fault. Our tsunami simulation from the coseismic deformation of the seismically estimated strike‐slip faulting produced a tsunami comparable to the leading part of the observation at Pantoloan. In order to reconstruct the detailed slip distribution on the fault plane, we then jointly utilized the tsunami waveform and Synthetic Aperture Radar (SAR) data. Because of the lack of SAR data in the bay, the tsunami data is necessary to constrain the offshore slip distribution, which directly induces the tsunami. The inverted source model shows a strike‐slip fault which consists of three segments extending from the epicenter to the south of 1.4°S with two bends and two asperities around Palu city. The joint inversion model accurately reconstructs the observed surface displacements and the leading part of the tsunami waveform. Our result exhibits the significant contribution of the strike‐slip faulting to the tsunami, but it also suggests additional tsunami sources, such as landslides, for the high inundations near Palu bay. The result also indicates that regional devastating tsunamis can be generated by an onshore strike‐slip fault with localized large dip slip. Plain Language Summary: The Palu, Indonesia, earthquake of September 28, 2018 produced tsunami flooding and damage in Palu city. Because of its strike‐slip mechanism, which is typically not efficient to produce tsunamis, multiple submarine landslides have been speculated as a tsunami source. We found that the fault model estimated by teleseismic waves (recorded globally outside Indonesia) can reproduce the tsunami recorded at the Pantoloan station in Palu bay. This indicates that the source of tsunami recoded at Pantoloan is mostly the fault motion due to the earthquake. We then combined the displacements measured by Synthetic Aperture Radar images and the Pantoloan tsunami waveform to estimate the detailed slip distribution on the fault. The slip model shows a strike‐slip fault with two large slip areas located near Palu city between two bends. This model well reproduces the Pantoloan tsunami but fails to fully reproduce the inundations in Palu city, suggesting that additional tsunami sources, such as landslides, should be responsible for the large inundations in Palu city. Our result suggests that a strike‐slip fault can induce a devastating local tsunami. Key Points: Two analyses utilizing teleseismic, Synthetic Aperture Radar, and tsunami data retrieve an earthquake source model that explains the observed tsunami A strike‐slip fault with localized large dip slip of the 2018 Palu earthquake induced the devastating regional tsunami Onshore strike‐slip faults should also be regarded as a potential source of tsunamis for regional areas